Pengaruh rasio regangan terhadap perilaku Llow Cycle Fatigue (LCF) paduan Al 7075-T7 - Santoso, Aribeni; Badaruddin, Mohammad; Savetlana, Shirley (MECHANICAL ; Jurnal Ilmiah Teknik Mesin, 2019)
The aluminium 7075 alloy is widely used in the aircraft industry for components on the front spar, stabilizer, frames that requires a high strength and low density ratio.The aerospace and automotive industries need to design for lightweight materials, where aluminum alloys are often used as the main component.Aluminum alloyshave good corrosion resistance properties. This material is used in a wide field not only for household appliances but also for industrial purposes, for example air-craft, car, marine and other constructions.The phenomenon of ductility decreasing due to pre-fatigue deformation, is the most significant for the combination of long pre-fatigue time, high humidity, and low strain rate.The process of making specimen shapes and dimensions were prepared according to ASTM E8 standard for the tensile specimens and ASTM E606 standardfor LCF test, respectively. Characterization of changes in material structures and the types of failure that occuredwerecarried out using OM, SEM and EDX.